علاقة إدارة الوقت بالإبداع الإداري "دراسة ميدانية في ديوان مجلس النواب في ليبيا" (Economic studies journal, 2023)
The aim of this study was to identify the relationship between time management and individual administrative creativity. A descriptive survey strategy was used the study. Respondents included (200) individuals. Data were collected, validated and verified using a questionnaire through which (2) scopes and (26) items, were covered. The study showed that all scopes were sensitive to the variable sample responses. It was also noticeable response to educational qualifications and ages. A strong correlation between time management and administrative creativity was absolutely obvious. It was highly recommended prioritizing tasks at work in norm of the significance(s), clarify tasks for employees, time management training and considering perks in an atmosphere that encourages creativity.
Keywords: Time management; Administration creativity; Correlation